Tools and algorithms for the construction and analysis of systems : 24th International Conference, TACAS 2018, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2018, Thessaloniki, Greece, April 14-20, 2018, Proceedings.: 24th International Conference, TACAS 2018, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2018, Thessaloniki, Greece, April 14-20, 2018, Proceedings. Part II (2018) - Unknown
No abstract available